2022
DOI: 10.1016/j.ynpai.2021.100081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of calcium-sensitive adenylyl cyclase AC1 and AC8 mRNA expression in the anterior cingulate cortex of mice with spared nerve injury neuropathy

Abstract: Highlights AC1 and AC8 are widely expressed in many regions of the mouse brain including the hippocampus, ACC, medial prefrontal cortex and midbrain regions, but AC1 is more highly expressed. Findings suggest a potential role for AC8 in anxiety-like behaviors caused by spared nerve injury in mice. SNI causes an increase in AC8 mRNA expression in NMDAR-2B (Nr2b) positive neurons in the contralateral ACC but does not affect AC1 mRNA expression.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…5 The Ca++ combines with calmodulin to activate adenylyl cyclase-1 (AC-1). AC-1 is one of the 10 subtypes of adenylate cyclase and is the predominant type in the ACC ( Shiers et al. 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…5 The Ca++ combines with calmodulin to activate adenylyl cyclase-1 (AC-1). AC-1 is one of the 10 subtypes of adenylate cyclase and is the predominant type in the ACC ( Shiers et al. 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to differences in AC1- or AC8-CaM interactions, since CaM has one mode of interaction with the C1b domain of AC1, whereas it can interact with the N-terminal domain and the C2b domain of AC8. Although we screened and selected for AC1-selective inhibitors, it is possible that AC8 inhibition could be beneficial for anxiety associated with various chronic and inflammatory pain states in humans and rodents (see ( Shiers et al, 2022 ) and references therein). Multiple studies have reported that AC8 knockout mice exhibited reduced anxiety-like behaviors in the elevated plus maze test ( Schaefer et al, 2000 ; Bernabucci & Zhuo, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported that AC8 knockout mice exhibited reduced anxiety-like behaviors in the elevated plus maze test ( Schaefer et al, 2000 ; Bernabucci & Zhuo, 2016 ). Furthermore, Shiers et al showed that Adcy8 mRNA expression increased in the anterior cingulate cortex (ACC) in a mouse model of neuropathic pain, although AC8 knockout does not play a role in mechanical hypersensitivity after inflammation ( Wei et al, 2002 ; Shiers et al, 2022 ). This suggests a potential role of AC8 in anxiety-like behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The sural nerve isn't altered, thus it's safe. The method is known as sparing nerve injury since the two additional nerves (the common fibular or tibial) are segmented (Shiers et al, 2022). Any straining or contact with the sural nerve that has been spared has to be avoided.…”
Section: Sni (Spared Nerve Injury)mentioning
confidence: 99%